1986
DOI: 10.1002/hed.2890080306
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative simultaneously administered cis‐platinum plus radiation therapy for advanced squamous cell carcinoma of the head and neck

Abstract: Synchronously administered cis-platinum (cis-DDP) and radiation therapy have been used to treat unresectable squamous cell carcinomas of the head and neck. The purpose of this study was to evaluate the efficacy and tolerance of preoperative adjuvant cis-DDP plus radiation therapy in operable stage III and IV head and neck cancers. Radiation therapy (4,500 rad) was delivered in 180-rad daily fractions. Cis-DDP (20 mg/M2) was given before radiotherapy on days 1-4 and 21-24. Eighteen patients began therapy; 16 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“… 12 Although such synergistic effects have been investigated for various chemotherapy agents such as hydroxyurea, 13 misonidazole, 14 mitomycin C, 15 and 5‐fluorouracil (5‐FU), 16,17 it is the platinum‐based compounds which have been widely studied and have met with the greatest success. 5,8,12,18,19 Conventional protocols adhere to the intravenous route of chemotherapy, but targeted intra‐arterial administration has the advantage of allowing higher doses to reach the tumor bed with minimal potential for the occurrence of systemic toxicity. 20 …”
Section: Introductionmentioning
confidence: 99%
“… 12 Although such synergistic effects have been investigated for various chemotherapy agents such as hydroxyurea, 13 misonidazole, 14 mitomycin C, 15 and 5‐fluorouracil (5‐FU), 16,17 it is the platinum‐based compounds which have been widely studied and have met with the greatest success. 5,8,12,18,19 Conventional protocols adhere to the intravenous route of chemotherapy, but targeted intra‐arterial administration has the advantage of allowing higher doses to reach the tumor bed with minimal potential for the occurrence of systemic toxicity. 20 …”
Section: Introductionmentioning
confidence: 99%
“…1 In an effort to improve outcomes, a number of concurrent chemoradiotherapy schedules have been investigated. Trials evaluating concurrent chemoradiotherapy have utilized radiosensitizing agents, such as hydroxyurea, 2 cisplatin, [3][4][5] and carboplatin. 6 Phase II studies from the Radiation Therapy Oncology Group (RTOG) and the Eastern Cooperative Oncology Group (ECOG) utilizing high-dose cisplatin regimens showed promising response and survival rates.…”
mentioning
confidence: 99%
“…Concurrent chemotherapy and radiation therapy trials have demonstrated a benefit to the combined synergism shown by a variety of radiosensitive agents such as hydroxyurea [34], misonidazole [35,36], mitomycin C and cisplatin [37][38][39], and cisplatin plus FU [40]. Radiation therapy combined with cisplatin therapy [41][42][43] has been associated with high levels of partial and complete tumor response in patients with locally advanced head and neck cancer.…”
Section: Head and Neck Cancermentioning
confidence: 99%